Exploring EFL Learning Barriers and Support Mechanisms of Indonesian Middle Socio-Economic Status Learners - Azzahra, Jasmine Aussie; Purnawan, Ari (Universitas Pendidikan Mandalika, 2025)
A learner's EFL learning can be affected by various factors, one of which is socio-economic status (SES), with most Indonesians belonging to the middle SES. This study employs a case study approach and semi-structured interviews to explore the barriers faced by middle SES Indonesians in EFL learning and the potential support mechanisms. The findings reveal three key themes: support from surroundings, access to learning resources, and self-efficacy. Support from surroundings and resource access are interrelated external factors, highlighting the importance of ease of access in the learning environment. Conversely, self-efficacy reflects learners' internal beliefs in their ability to succeed in EFL. The study suggests several support mechanisms, such as providing equitable opportunities for practice, enhancing access to learning materials, and fostering a supportive educational environment. Resources like visual aids, culturally relevant materials, and free language platforms can significantly benefit not only middle SES learners but others as well. Despite these insights, the study has limitations, including reliance on interviews and a small participant pool of four graduates. Future research should utilize multiple instruments and larger, more diverse samples for stronger findings. The insights gained can inform policymakers, educators, and families in enhancing EFL implementation, emphasizing that support should also come from home. Implementing educational policies that address the needs of all socio-economic classes can make learning more relevant and engaging.